Beneficial role of silibinin in monitoring the cadmium induced hepatotoxicity in Albino Wistar rats - Srinivasan, R; Ramprasath, C (Recent Research in Science and Technology, 2012)
Cadmium (Cd), an environmental toxic pollutant affects many organs in human beings specially the liver and kidney. In this study, Cd (3 mg/kg body weight (b.w.)) was subcutaneously administered to rats for 3 weeks, which shows significantly (P<0.05) increase in the activities of serum transaminases, alkaline phosphatase and lactate dehydrogenase, with significant elevation of lipid peroxidation along with significant (P<0.05) decreased in the levels of antioxidants in the liver. Oral administration of silibinin (SB) at 80 mg/kg b.w. significantly normalized the activities of serum hepatic enzymes and reduced the levels of lipid peroxidation and also restored the antioxidant defense in the liver when compared to other doses of SB (20 and 40 mg/kg b.w.). Histopathological analysis of liver was consistent with the biochemical findings. From this study we conclude the curative potential of SB against Cd- induced hepatic injury.Â Â